O Painel II – O cartel e sua prova – busca e apreensão: experiência comparada - Grinberg, Mauro; Zanotta, Pedro; Prado, Luiz Carlos Delorme; Rosenberg, Barbara; Kwinter , Robert; Niggemann, Peter; Gyselen, Luc (Revista do IBRAC, 2024)
Mauro Grinberg .................... 75 Pedro Zanotta .................... 76 Luiz Carlos Delorme Prado .................... 76 Barbara Rosenberg .................... 84 Robert Kwinter .................... 99 Peter Niggemann .................... 129 Luc Gyselen .................... 140 DEBATE .................... 149